2015
DOI: 10.18404/ijemst.15099
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Survival Rates in Engineering for Community College Transfer Students Using Grades in Calculus and Physics

Abstract: This study uses a unique synthesized set of data for community college students transferring to engineering by combining several cohorts of longitudinal data along with transcript-level data, from both the Community College and the University, to measure success rates in engineering. The success rates are calculated by developing Kaplan-Meier survival curves measuring retention in engineering over time by grades received in Calculus and Physics courses at both institutions. For each course, survival curves are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…The courses completed at the sending institution also have a significant impact on the student's persistence at the receiving institution. Specifically, according to the literature reviewed in this work, students should complete as many core engineering‐related courses as possible and should have Calculus I and II, as well as one semester of physics at a minimum (Darrow, 2012; Laugerman, Rover, Shelly, & Mickelson, 2015; Laugerman & Shelley, 2013; Laugerman, Shelley, Rover, & Mickelson, 2015). Additionally, the student's overall grade point average (GPA) from their sending institution was shown to be a strong determinant of engineering transfer student persistence (Anderson‐Rowland, 2011; Lakin & Cardenas Elliott, 2016; Lopez & Jones, 2017; Lopez, 2012; Shields & Pietroburgo, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The courses completed at the sending institution also have a significant impact on the student's persistence at the receiving institution. Specifically, according to the literature reviewed in this work, students should complete as many core engineering‐related courses as possible and should have Calculus I and II, as well as one semester of physics at a minimum (Darrow, 2012; Laugerman, Rover, Shelly, & Mickelson, 2015; Laugerman & Shelley, 2013; Laugerman, Shelley, Rover, & Mickelson, 2015). Additionally, the student's overall grade point average (GPA) from their sending institution was shown to be a strong determinant of engineering transfer student persistence (Anderson‐Rowland, 2011; Lakin & Cardenas Elliott, 2016; Lopez & Jones, 2017; Lopez, 2012; Shields & Pietroburgo, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Laugerman, Rover, and Mickelson estimated retention rates in engineering programs for a group of approximately 1200 transfer students, using grades from Calculus I and II, and Physics I. They found that high grades in the introductory calculus courses seemed to be a higher predictor of retention than physics, suggesting that high achievers in mathematics are more likely to overcome the initial difficulty identified by Zhang and Ozuna [10].…”
Section: Transfer Challengesmentioning
confidence: 99%
“…The fact that Ontario is late to the systematic transfer game does present an opportunity to learn from other approaches (Fitz Gibbon, 2014;Trick, 2013), and leverage activity underway at the institutions. There is a rich body of literature on different transfer models and systems in North America and Europe (Finlay, 2009;Laugerman, Rover, Shelley, & Mickelson, 2015), and the role and responsibilities of learning outcomes in articulation and transfer (Goff et al, 2015;Lennon et al, 2014;Ontario Ministry of Training Colleges and Universities, 2010;Timney, 2010). Learning outcomes can potentially enhance the credit transfer systems by providing evidence-based comparison of course content and the context of learning (Carter, Coyle, & Leslie, 2011;Fitz Gibbon, 2014).…”
mentioning
confidence: 99%